2015
DOI: 10.1016/j.clcc.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Delayed Hypersensitivity Reactions to a Single Dose of Oxaliplatin

Abstract: • A review of the literature found two similar cases of delayed reactions to oxaliplatin occurring 20 and 10 hours after infusion respectively. The first case occurred after the initial dose and again with cycle 2. The second case happened following the sixth infusion.• This is the first reported case of immediate and delayed hypersensitivity reactions occurring following the initial dose of oxaliplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The usually encountered adverse reaction is peripheral neuropathy which can be acute or chronic. 7 Hypersensitivity reactions to oxaliplatin, which are type I in nature, have been reported in about 10-25% of cases, whereas cases of severe hypersensitivity reported is only 0.5%. 1,7,8 Features of hypersensitivity reactions include minor reactions like rash, urticaria, flushing, itching, abdominal cramps, diarrhoea, and back pain and severe symptoms can manifest as tachycardia, bronchospasm, stridor, dysphonia, hypotension or hypertension and seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usually encountered adverse reaction is peripheral neuropathy which can be acute or chronic. 7 Hypersensitivity reactions to oxaliplatin, which are type I in nature, have been reported in about 10-25% of cases, whereas cases of severe hypersensitivity reported is only 0.5%. 1,7,8 Features of hypersensitivity reactions include minor reactions like rash, urticaria, flushing, itching, abdominal cramps, diarrhoea, and back pain and severe symptoms can manifest as tachycardia, bronchospasm, stridor, dysphonia, hypotension or hypertension and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…7 Hypersensitivity reactions to oxaliplatin, which are type I in nature, have been reported in about 10-25% of cases, whereas cases of severe hypersensitivity reported is only 0.5%. 1,7,8 Features of hypersensitivity reactions include minor reactions like rash, urticaria, flushing, itching, abdominal cramps, diarrhoea, and back pain and severe symptoms can manifest as tachycardia, bronchospasm, stridor, dysphonia, hypotension or hypertension and seizures. 9 The incidence of laryngospasm due to oxaliplatin, is less when compared to other adverse effects but can be fatal if not diagnosed and managed early.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were no allergic reactions or cardiotoxicity during transarterial infusion with raltitrexed, and no studies to date have reported any adverse events in this context. In contrast, allergic reactions and cardiotoxicity frequently occur when antitumor drugs such as oxaliplatin and epirubicin are used [ 10 , 21 - 23 ]. These results indicate that the combination of raltitrexed and oxaliplatin in TACE in patients with unresectable HCC is safe and tolerable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our figures showed that no patients experienced allergic reactions while HAI with raltitrexed, and no studies have reported allergic reactions to raltitrexed. However, allergic reactions related to oxaliplatin, epirubicin, and other anti-cancer drugs are frequently reported in the literature [17,21,22].…”
Section: Discussionmentioning
confidence: 99%